Analisis Faktor Fundamental Terhadap Return Saham (Studi Kasus Pada Sub Sektor Telecommunication yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2023) - Septi Wulandari; Diah Yudhawati; Angga Prasetia (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
The aim of this research is to determine the effect of Total Assets Turnover (TAT), Net Profit Model (NPM), and Debt to Equity Ratio (DER) on stock returns in telecommunications subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2023 period. The population in this study consisted of 5 telecommunications subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2023 period. The sampling technique uses the purpose sampling method. The type of data used in this research is quantitative data with descriptive analysis, panel data regression, classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination test. The selected model is the Common Effect Model (CEM). The research results show that Total Asset Turnover (TAT (X1)) and Debt to Equity Ratio (DER(X3)) partially have no significant effect on stock returns, while Net Profit Margin (NPM (X2)) partially has a significant effect on stock returns. Simultaneous data analysis shows that Total Asset Turnove (TAT (X1)), Net Profit Margin (NPM (X2)), and Debt to Equity Ratio (DER (X3)) have a significant effect on stock returns.